In vitro Inhibition of HIV-1 by Cyclotide-Enriched Extracts of Viola tricolor - Conzelmann, Carina; Muratspahić, Edin; Tomašević, Nataša; Münch, Jan; Gruber, Christian W. (Frontiers in Pharmacology, 2022)
Since viral infectious diseases continue to be a global health threat, new antiviral drugs are urgently needed. A unique class of therapeutic compounds are antimicrobial peptides (AMPs). They can be found in humans, bacteria and plants. Plants express a wide variety of such defense peptides as part of their innate immune system to protect from invading pathogens. Cyclotides are non-classical AMPs that share a similar structure. Their unique topology consists of a circular peptide backbone and disulfide bonds. In previous studies they have been attributed to a wide range of biological activities. To identify novel cyclotides with antiviral activity, we established a library of plant extracts largely consisting of cyclotide-rich species and screened them for inhibitors of HIV-1 infection. Subsequent extraction and fractionation revealed four cyclotide-containing subfractions from Viola tricolor with antiviral activity. These subfractions inhibited HIV-1 infection with IC50 values between 0.6 and 11.2 µg/ml, and selectivity indices of up to 8.1. The identification and characterization of antiviral cyclotides and the determination of the antiviral mechanisms may allow to develop novel agents to combat viral infections. Therefore, cyclotides represent a natural source of bioactive molecules with prospects for development as therapeutics.